STUDI AKSESIBILITAS ZONA POLIKLINIK DI RSUD GAMBIRAN TERHADAP PASIEN DENGAN ALAT BANTU JALAN: STUDI AKSESIBILITAS ZONA POLIKLINIK DI RSUD GAMBIRAN TERHADAP PASIEN DENGAN ALAT BANTU JALAN - Silvya Bintang Ayu Candradewi (Ide dan Dialog Desain Indonesia (Idealog), 2025)
Abstract : The availability of accessible circulation spaces in building design and furniture layout in several hospital facilities in Indonesia is still not optimal. Patients with reduced bodily function or physical mobility limitations have difficulty walking; they require mobility aids and must adapt to hospital conditions. At Gambiran Regional General Hospital, patients using mobility aids accompanied by caregivers are most commonly found in the outpatient clinic zone. The research problem is indicated by the fact that not all accessibility features of the outpatient clinic building can be easily navigated by users of mobility aids when visiting and accessing the outpatient clinic zone at Gambiran Regional General Hospital. The objective of this study is to evaluate the level of outpatient clinic accessibility by identifying, through an approach based on universal design principles, the accessibility of the outpatient clinic zone at Gambiran Regional General Hospital for patients using ABJ and their caregivers. The research method employed a descriptive qualitative approach with a case study of the outpatient clinic zone at Gambiran Regional General Hospital through observation and analysis of accessibility phenomena. The observation instrument utilized a table of indicators based on the seven principles of universal design. Subsequently, a questionnaire was distributed to the research sample. The questionnaire instrument employed indicators based on building accessibility principles. The research sample consisted of a pair of patients using mobility aids (ambulatory, wheelchair, and stretcher) and their caregivers.The questionnaire results will be analyzed using descriptive statistical analysis, presented in tables categorizing the instrument’s scale, using SPSS version 26. The analysis will identify differences in parameter values, which will then be compared using a comparison table. The results of this study indicate that there are accessibility barriers for patients with ABJ in the outpatient clinic area of Gambiran Regional General Hospital. Keywords : Accessibility, Universal Design, Polyclinic Zones, Walking Aid